2020
DOI: 10.12659/msmbr.920449
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of 24 Weeks of Combined Schroth and Pilates Exercises on Cobb Angle, Angle of Trunk Rotation, Chest Expansion, Flexibility and Quality of Life in Adolescents with Idiopathic Scoliosis

Abstract: Departmental sources Background: This study aimed to quantify the outcomes of combining Schroth and Pilates exercises on the Cobb angle, angle of trunk rotation (ATR), chest expansion, flexibility (trunk flexion), and quality of life (QoL) in adolescents with mild and moderate idiopathic scoliosis. Material/Methods: Sixty-nine adolescents with idiopathic scoliosis aged 10-17 years, presenting with a Cobb angle of 10-45º were enrolled in this study. The treatment protocol, including selected exercises from Schr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 37 publications
(59 reference statements)
0
39
0
2
Order By: Relevance
“…In conservative treatment, increasing the flexibility and mobility of the spine is important to correct the curve of the spine in scoliosis [ 43 ]. The effect of the Schroth method on the flexibility and mobility of the spine has been documented in previous studies [ 7 , 44 , 45 ]. Malaj et al [ 44 ] reported an improvement in trunk flexion after treatment with combined Schroth and Pilates exercises in patients with AIS.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In conservative treatment, increasing the flexibility and mobility of the spine is important to correct the curve of the spine in scoliosis [ 43 ]. The effect of the Schroth method on the flexibility and mobility of the spine has been documented in previous studies [ 7 , 44 , 45 ]. Malaj et al [ 44 ] reported an improvement in trunk flexion after treatment with combined Schroth and Pilates exercises in patients with AIS.…”
Section: Discussionmentioning
confidence: 89%
“…The effect of the Schroth method on the flexibility and mobility of the spine has been documented in previous studies [ 7 , 44 , 45 ]. Malaj et al [ 44 ] reported an improvement in trunk flexion after treatment with combined Schroth and Pilates exercises in patients with AIS. Another study examined the effects of CS exercise on flexibility in scoliosis and showed that lumbar flexibility increased significantly after CS exercise in patients with AIS [ 13 ].…”
Section: Discussionmentioning
confidence: 89%
“…Sport can be synonymous with “harmonic” prevention activities, such as Pilates, which can improve the expansion of the rib cage and the flexibility of the trunk [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prieš ir po dviejų mėnesių tiriamiesiems buvo įvertintas liemens funkcinis stabilumas, juosmeninės ir krūtininės stuburo dalies paslankumas, GPT, FIT 1 . Pirmos ir antros grupių tiriamiesiems stuburo korekcija taikyta Schroth metodu, atliekant stuburo kreivių stabilizavimo, stuburo mobilizacijos, laikysenos išilginimo, derotacijos, raumenų kontrolės, jėgos ir ištvermės pratimus (Rrecaj-Malaj et al, 2020). Antros grupės tiriamiesiems po Schroth metodo užsiėmimų buvo taikytas kineziologinis teipavimas.…”
Section: įVadasunclassified